APLIKASI MONITORING PELAYANAN MASYARAKAT DESA SUMBERANYAR KECAMATAN PAITON BERBASIS WEB - Ruly Amalia; Anis Yusrotun N.; Wali Ja’far Shudiq (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Public service is a task that must be carried out by the government. However, community services in Sumberanyar Village, especially in responding to aspirations and complaints such as complaints about social assistance, infrastructure and other complaints are still done manually and have not been published properly, one of the factors is time. The distance from their home address to the village office is a barrier factor for them and the size of the source area is an obstacle and the community has to wait a long time for their complaints to be processed. Therefore, it is necessary to have an application that can facilitate the community in carrying out aspirations services, the web-based application for monitoring community services in Sumberanyar Village, Paiton District, is a solution to overcome the problems that have been described. This application was built using the Waterfall SLDC (Software Development Life Cycle) model and it is hoped that by doing this research benefits can be taken such as making it easier for village officials to respond to village community service aspirations.